Normative Stock Price Models - Bierman, Harold; Hass, Jerome (Journal of Financial and Quantitative Analysis, 1971)
All the stock price models discussed in this paper are based on the assumption that the present value of a share of common stock is equal to the discounted value of all future expected dividends accruing to the stockholder:where Po : current value of a share of common stock, Dt: dividend expected to be received at end of period t, k : investor's discount or time-value rate, andt : time.